Motion Artifact Reduction in Contrast-Enhanced Dual-Energy Mammography – A Multireader Study about the Effect of Nonrigid Registration as Motion Correction on Image Quality - Sistermanns, Markus; Kowall, Bernd; Hörnig, Mathias; Beiderwellen, Karsten; Uhlenbrock, Detlev (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2021)
Purpose The technically caused delay between low-energy (LE) and high-energy (HE) acquisitions allows motion artifacts in contrast-enhanced dual-energy mammography (CEDEM). In this study the effect of motion correction by nonrigid registration on image quality of the recombined images was investigated.Materials and Methods Retrospectively for 354 recombined CEDEM images an additional recombined image was processed from the raw data of LE and HE images using the motion correction algorithm. Five radiologists with many years of experience in breast cancer diagnostic imaging compared side-by-side one conventional processed CEDEM image with the corresponding image processed by the motion correction algorithm. Every pair of images was compared based on six criteria: General image quality (1), sharpness of skin contour (2), reduction of image artifacts (3), sharpness of lesion contour (4), contrast of lesion (5), visibility of lymph nodes (6). These criteria were rated on a Likert scale (improvement: + 1, + 2; deterioration: –1, –2).Results The mean ratings concerning criteria 1–5 showed a superiority of the recombined images processed by the motion correction algorithm. For example, the mean rating of general image quality was 0.86 (95 % CI: 0.78; 0.93). Only the mean rating concerning criterion 6 showed an inferiority of the recombined images processed by the motion correction algorithm (–0.29 (–0.46; –0.13)).Conclusion The usage of nonrigid registration for motion correction significantly improves the general image quality and the quality of subordinate criteria on the recombined CEDEM images at the expense of somewhat reduced lymph node visibility in some cases.Key Points: Citation Format
Keywords: mammography; artifacts; breast; image processing